Three-dimensional constitutive model for elastic-plastic behaviour of fibre-reinforced composites. (15th May 2018) - Skovsgaard, Simon P.H.; Jensen, Henrik Myhre
Abstract: A formulation of a three-dimensional homogenized constitutive model is developed that can predict strain localization in fibre-reinforced composites. A constitutive equation for the model is developed in a general rate form based on independent constituent behaviour which can be either elastic or elastic-plastic. The performance of the constitutive model is investigated by performing an infinite kink band analysis. The development of a kink band is investigated for several initial imperfections and compared with previously published results.